Ordinances of the City of Burlington, with Head Notes and an Analytic Index, § 1 (1841), at 149-150 (Chas. Ben. Darwin, Thompson & Co. Printers, 1856) - (:unkn) unknown (General Publisher, 1841)
Allowed the mayor and aldermen of the city to authorize a committee on internal improvements to give requirements and regulations before approval of shooting batteries may be given.
--
Keywords: SHOOTING RANGES OR GALLERIES